2013
DOI: 10.1111/eva.12059
|View full text |Cite
|
Sign up to set email alerts
|

Crop‐to‐wild gene flow and spatial genetic structure in the closest wild relatives of the cultivated apple

Abstract: Crop‐to‐wild gene flow have important evolutionary and ecological consequences and require careful consideration in conservation programs for wild genetic resources of potential use in breeding programs and in assessments of the risk of transgene escape into natural ecosystems. Using 26 microsatellites and a set of 1181 trees, we investigated the extent of introgression from the cultivated apple, Malus domestica, to its three closest wild relatives, M. sylvestris in Europe, M. orientalis in the Caucasus, and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(98 citation statements)
references
References 56 publications
(141 reference statements)
5
89
4
Order By: Relevance
“…The suitability for population genetic analysis of the markers used was demonstrated in previous studies (Cornille et al. , ,b).…”
Section: Methodsmentioning
confidence: 91%
See 4 more Smart Citations
“…The suitability for population genetic analysis of the markers used was demonstrated in previous studies (Cornille et al. , ,b).…”
Section: Methodsmentioning
confidence: 91%
“…Since its introduction into Europe by humans 1500 years ago, the cultivated apple has acted as a source of genes for introgression into the European wild apple (Cornille et al. ). We found that the rates of crop‐to‐wild introgression varied across Europe and could be accounted for by direct and indirect anthropogenic factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations